A lithium-carbon composite negative electrode sheet, battery and all-solid-state battery
By introducing LiC6 layer into the negative electrode sheet of the lithium battery, the problem of lithium dendrites generated during the circulation of lithium batteries is solved, the uniform deposition of lithium ions and the cycle life of the battery are improved, and the safety and mass energy density of the battery are enhanced.
Patent Information
- Application Number
- CN202310817910.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-05
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-07-05
AI Technical Summary
Existing lithium batteries are prone to lithium dendrites during circulation, resulting in safety accidents such as diaphragm puncture, internal short circuit, thermal runaway and explosion; while using lithium indium alloy as the negative electrode can guide the uniform deposition of lithium ions, due to the high density of indium metal, the energy density of the battery mass decreases.
A lithium-carbon composite negative electrode sheet is adopted, and its structure includes a lithium layer, a carbon layer and a LiC6 layer. The LiC6 layer is located between the lithium layer and the carbon layer. The lithium-philic interface layer LiC6 is formed by applying pressure by an isostatic press, which increases the layer spacing, improves the electronegative nature of carbon atoms, enhances the bonding between lithium ions and carbon, and guides the uniform deposition of lithium ions.
Effectively inhibit the volume changes, dendrite growth and pulverization caused by lithium deposition, improve the circulating Coulomb efficiency of electrode materials, extend the cycle life of the battery, and improve the safety and mass energy density of the battery.
Smart Images

Figure CN116845182B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to a lithium-carbon composite negative electrode sheet, a battery and an all-solid-state battery Background Art
[0002] When lithium metal negative electrodes are used in batteries, uneven lithium ion deposition during the battery cycle can easily produce lithium dendrites. The growth of lithium dendrites can easily pierce the diaphragm, causing an internal short circuit in the battery, thereby causing thermal runaway and battery explosions and other safety accidents.
[0003] To solve the above problems, the commonly used method is to use lithium alloy as the negative electrode to guide the uniform deposition of lithium ions. For example, lithium-indium alloy can well guide the deposition of lithium ions and alleviate the problem of lithium dendrite growth. However, the density of indium metal (7.30g / cm 3 ) is significantly higher than lithium metal (0.534 g / cm 3 ), the introduction of indium metal leads to a significant increase in the density of lithium-indium alloy, which significantly increases the mass of the negative electrode sheet of the same volume and reduces the mass energy density of the battery.
[0004] In the prior art, lithium metal is often combined with carbon to form a Li-C composite material. However, the current Li-C composite material cannot construct a perfect electronic network framework and cannot guide the uniform deposition of lithium ions. Summary of the invention
[0005] In order to solve the above-mentioned defects in the prior art, one of the objectives of the present invention is to provide a lithium-carbon composite negative electrode sheet to guide the uniform deposition of lithium ions.
[0006] In order to solve the above-mentioned defects in the prior art, a second object of the present invention is to provide a battery with a longer cycle life.
[0007] In order to solve the above-mentioned defects in the prior art, the third object of the present invention is to provide an all-solid-state battery with higher cycle performance and capacity characteristics.
[0008] The technical solution provided according to one of the purposes of the present invention is as follows:
[0009] A lithium-carbon composite negative electrode sheet comprises: a lithium layer, a carbon layer and a LiC6 layer, wherein the LiC6 layer is arranged between the lithium layer and the carbon layer, and the lithium-carbon composite negative electrode sheet has a 001 characteristic diffraction peak in the range of 23.66°-24.15° in an X-ray diffraction spectrum.
[0010] The lithium-carbon composite negative electrode sheet of the present invention contains a LiC6 layer, which increases the interlayer spacing of the lithium-carbon composite negative electrode sheet, is beneficial to the deintercalation of lithium ions during the charge and discharge process, and improves the electronegativity of carbon atoms, enhances the bonding between carbon and lithium ions, can guide the uniform deposition of lithium ions, and effectively inhibits the volume change, dendrite growth and pulverization caused by lithium deposition, thereby improving the cycle coulomb efficiency of the electrode material.
[0011] The technical solution provided according to the second object of the present invention is as follows:
[0012] A battery comprises the above-mentioned lithium-carbon composite negative electrode sheet.
[0013] Because the lithium-carbon composite negative electrode sheet contains a LiC6 layer, it can guide the uniform deposition of lithium ions, thereby improving the cycle life and safety of the battery.
[0014] The technical solution provided according to the third object of the present invention is as follows:
[0015] An all-solid-state battery comprises the above-mentioned lithium-carbon composite negative electrode sheet.
[0016] During the assembly process of the all-solid-state battery, the solid electrolyte sheet and the positive and negative electrode sheets are pressed together. Due to the soft texture of metallic lithium, the lithium layer may be deformed during the pressing process, partially embedded in the pores of the carbon layer, and even extend into the solid electrolyte layer. The positive electrode will also squeeze the solid electrolyte layer during the pressing process, which may cause the negative electrode lithium layer to short-circuit with the positive electrode, causing short-circuit self-discharge in the battery, affecting the battery life. The lithium-carbon composite negative electrode sheet of the present invention is formed with a LiC6 layer, which has a high structural strength and is not easily deformed under high pressure. A protective barrier can be formed between the lithium layer and the solid electrolyte layer to avoid the occurrence of internal short circuits during the pressing process of assembling the battery, thereby improving the reliability and yield of the production of all-solid-state batteries. In addition, since the Li C6 layer can guide the uniform deposition of lithium ions, the cycle life of the all-solid-state battery can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 A cross-sectional view of the lithium-carbon composite negative electrode sheet prepared in Example 1;
[0018] Figure 2 XRD diagram of the lithium-carbon composite negative electrode sheet prepared in Comparative Example 1
[0019] Figure 3 XRD pattern of the lithium-carbon composite negative electrode sheet prepared in Example 2;
[0020] Figure 4 This is a SEM image of the lithium-carbon composite negative electrode sheet prepared in Example 1;
[0021] Figure 5This is the SEM image of the lithium-carbon composite negative electrode sheet prepared in Comparative Example 2. DETAILED DESCRIPTION
[0022] For better understanding and implementation, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0023] In the description of the present invention, it should be noted that the terms "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside" and "outside" etc. indicating directions or positional relationships are based on the directions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore cannot be understood as a limitation on the present invention.
[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0025] In the present invention, the copper-lithium composite belt is composed of a lithium layer and a copper layer stacked together. The thickness of the lithium layer in each embodiment and comparative example containing the copper-lithium composite belt is the thickness of the lithium layer in the copper-lithium composite belt, not the overall thickness of the copper-lithium composite belt.
[0026] Example 1
[0027] This embodiment provides a method for preparing a lithium-carbon composite negative electrode sheet, comprising the following steps:
[0028] S1. Weigh artificial graphite and binder hydrogenated styrene-butadiene rubber in a mass ratio of 97:3;
[0029] S2. Add artificial graphite and hydrogenated styrene-butadiene rubber into xylene solvent to prepare carbon layer slurry, use a slurry mixer to mix the carbon layer slurry evenly, and then use a coating machine to coat the carbon layer slurry on a copper-lithium composite tape (lithium layer thickness is 50 μm±2 μm), place it in a vacuum oven at 60° C. and dry it for 4 hours to obtain a composite negative electrode sheet, and use a digital micrometer to measure the thickness of the carbon layer on the composite negative electrode sheet to be 20 μm±2 μm;
[0030] S3. Use a 10-ton double-roller to roll the composite negative electrode sheet, and then use an isostatic press to apply a pressure of 280 MPa to the composite negative electrode sheet and maintain the pressure for 5 minutes to obtain a lithium-carbon composite negative electrode sheet with a lithium-philic interface layer LiC6.
[0031] Example 2
[0032] This embodiment provides a method for preparing a lithium-carbon composite negative electrode sheet, comprising the following steps:
[0033] S1. Weigh artificial graphite and binder hydrogenated nitrile rubber in a mass ratio of 99:1;
[0034] S2. Add artificial graphite and hydrogenated nitrile rubber to xylene solvent to prepare a carbon layer slurry, use a slurry mixer to mix the carbon layer slurry evenly, and then use a coating machine to coat the carbon layer slurry on a lithium sheet with a thickness of 100 μm ± 3 μm, place it in a vacuum oven at 70° C. and dry it for 4 hours to obtain a composite negative electrode sheet, and use a digital micrometer to measure the thickness of the carbon layer on the composite negative electrode sheet to be 10 μm ± 1 μm;
[0035] S3. Use a 15-ton double-roller to roll the composite negative electrode sheet, then use an isostatic press to apply a pressure of 150 MPa to the composite negative electrode sheet and maintain the pressure for 15 minutes to obtain a lithium-carbon composite negative electrode sheet with a lithium-philic interface layer LiC6.
[0036] Example 3
[0037] This embodiment provides a method for preparing a lithium-carbon composite negative electrode sheet, comprising the following steps:
[0038] S1. Weigh Si / C powder (Si content is 5%wt) and binder hydrogenated styrene-butadiene rubber in a mass ratio of 99.9:0.1;
[0039] S2. Si / C powder (Si content is 5%wt) and hydrogenated styrene-butadiene rubber are added to xylene solvent to prepare a carbon layer slurry, and the carbon layer slurry is mixed evenly using a slurry mixer, and then the carbon layer slurry is coated on a copper-lithium composite tape (lithium layer thickness is 10μm±1μm) using a coating machine, and placed in a 45°C vacuum oven for 4 hours to obtain a composite negative electrode sheet, and the thickness of the carbon layer on the composite negative electrode sheet is measured by a digital micrometer to be 5μm±1μm;
[0040] S3. Use a 25-ton double-roller to roll the composite negative electrode sheet, then use an isostatic press to apply a pressure of 400 MPa to the composite negative electrode sheet and maintain the pressure for 30 minutes to obtain a lithium-carbon composite negative electrode sheet with a lithium-philic interface layer LiC6.
[0041] Example 4
[0042] This embodiment provides a method for preparing a lithium-carbon composite negative electrode sheet, comprising the following steps:
[0043] S1. Weigh Si / C powder (Si content is 7%wt) and binder hydrogenated styrene-butadiene rubber in a mass ratio of 99.9:0.1;
[0044] S2. Si / C powder (Si content is 7%wt) and hydrogenated styrene-butadiene rubber are added to xylene solvent to prepare a carbon layer slurry, and the carbon layer slurry is mixed evenly using a slurry mixer, and then the carbon layer slurry is coated on a copper-lithium composite tape (lithium layer thickness is 50μm±2μm) using a coating machine, and placed in a 60°C vacuum oven for drying for 4 hours to obtain a composite negative electrode sheet, and the thickness of the carbon layer on the composite negative electrode sheet is measured using a digital micrometer to be 10μm±1μm;
[0045] S3. Use a 25-ton double-roller to roll the composite negative electrode sheet, and then use an isostatic press to apply a pressure of 300 MPa to the composite negative electrode sheet and maintain the pressure for 30 min to obtain a lithium-carbon composite negative electrode sheet with a lithium-philic interface layer Li C6.
[0046] Example 5
[0047] This embodiment provides a method for preparing a lithium-carbon composite negative electrode sheet, comprising the following steps:
[0048] S1. Weigh Si / C powder (Si content is 20%wt) and binder hydrogenated styrene-butadiene rubber in a mass ratio of 99.9:0.1;
[0049] S2. Si / C powder (Si content is 20%wt) and hydrogenated styrene-butadiene rubber are added to xylene solvent to prepare a carbon layer slurry, and the carbon layer slurry is mixed evenly using a slurry mixer, and then the carbon layer slurry is coated on a copper-lithium composite tape (lithium layer thickness is 50μm±2μm) using a coating machine, and placed in a 45°C vacuum oven for 4 hours to obtain a composite negative electrode sheet, and the thickness of the carbon layer on the composite negative electrode sheet is measured using a digital micrometer to be 10μm±1μm;
[0050] S3. Use a 25-ton double-roller to roll the composite negative electrode sheet, and then use an isostatic press to apply a pressure of 400 MPa to the composite negative electrode sheet and maintain the pressure for 10 min to obtain a lithium-carbon composite negative electrode sheet with a lithium-philic interface layer Li C6.
[0051] Example 6
[0052] This embodiment provides a method for preparing a lithium-carbon composite negative electrode sheet, comprising the following steps:
[0053] S1. Weigh Si / C powder (Si content is 5%wt) and binder hydrogenated styrene-butadiene rubber in a mass ratio of 99.9:0.1;
[0054] S2. Si / C powder (Si content is 5%wt) and hydrogenated styrene-butadiene rubber are added to xylene solvent to prepare a carbon layer slurry, and the carbon layer slurry is mixed evenly using a slurry mixer, and then the carbon layer slurry is coated on a copper-lithium composite tape (lithium layer thickness is 15μm±1μm) using a coating machine, and placed in a 45°C vacuum oven for 4 hours to obtain a composite negative electrode sheet, and the thickness of the carbon layer on the composite negative electrode sheet is measured by a digital micrometer to be 3μm±0.5μm;
[0055] S3. Use a 10-ton double-roller to roll the composite negative electrode sheet, then use an isostatic press to apply a pressure of 150 MPa to the composite negative electrode sheet and maintain the pressure for 10 minutes to obtain a lithium-carbon composite negative electrode sheet with a lithium-philic interface layer LiC6.
[0056] Example 7
[0057] This embodiment provides a method for preparing a lithium-carbon composite negative electrode sheet, comprising the following steps:
[0058] S1. Weigh artificial graphite and binder hydrogenated nitrile rubber in a mass ratio of 99:1;
[0059] S2. Add artificial graphite and binder hydrogenated nitrile rubber into xylene solvent to prepare carbon layer slurry, use a slurry mixer to mix the carbon layer slurry evenly, and then use a coating machine to coat the carbon layer slurry on a 200 μm±5 μm thick lithium sheet, place it in a 70° C. vacuum oven and dry it for 4 hours to obtain a composite negative electrode sheet, and use a digital micrometer to measure the thickness of the carbon layer on the composite negative electrode sheet to be 80 μm±2 μm;
[0060] S3. Use a hot pressing plate to hot press the composite negative electrode sheet at a temperature of 30°C and a pressure of 30 MPa, then use an isostatic press to apply a pressure of 400 MPa to the composite negative electrode sheet and maintain the pressure for 30 minutes to obtain a lithium-carbon composite negative electrode sheet with a lithium-philic interface layer LiC6.
[0061] Example 8
[0062] This embodiment provides a method for preparing a lithium-carbon composite negative electrode sheet, comprising the following steps:
[0063] S1. Weigh artificial graphite and binder hydrogenated nitrile rubber in a mass ratio of 99:1;
[0064] S2. Add artificial graphite and binder hydrogenated nitrile rubber into xylene solvent to prepare carbon layer slurry, use a slurry mixer to mix the carbon layer slurry evenly, and then use a coating machine to coat the carbon layer slurry on a 100 μm±2 μm thick lithium sheet, place it in a 70° C. vacuum oven and dry it for 4 hours to obtain a composite negative electrode sheet, and use a digital micrometer to measure the thickness of the carbon layer on the composite negative electrode sheet to be 20 μm±2 μm;
[0065] S3. Use a 10-ton double-roller to roll the composite negative electrode sheet, and then use an isostatic press to apply a pressure of 150 MPa to the composite negative electrode sheet and maintain the pressure for 2 minutes to obtain a lithium-carbon composite negative electrode sheet with a lithium-philic interface layer LiC6.
[0066] Example 9
[0067] This embodiment provides a method for preparing a lithium-carbon composite negative electrode sheet, comprising the following steps:
[0068] S1. Weigh artificial graphite and binder hydrogenated styrene-butadiene rubber in a mass ratio of 99.9:0.1;
[0069] S2. Add artificial graphite and hydrogenated styrene-butadiene rubber into xylene solvent to prepare carbon layer slurry, use a slurry mixer to mix the carbon layer slurry evenly, and then use a coating machine to coat the carbon layer slurry on a lithium sheet with a thickness of 100 μm±3 μm, place it in a vacuum oven at 60° C. and dry it for 6 hours to obtain a composite negative electrode sheet, and use a digital micrometer to measure the thickness of the carbon layer on the composite negative electrode sheet to be 2 μm±1 μm;
[0070] S3. Use a 50-ton double-roller to roll the composite negative electrode sheet, and then use an isostatic press to apply a pressure of 600 MPa to the composite negative electrode sheet and maintain the pressure for 30 minutes to obtain a lithium-carbon composite negative electrode sheet with a lithium-philic interface layer LiC6.
[0071] Example 10
[0072] This embodiment provides a method for preparing a lithium-carbon composite negative electrode sheet, comprising the following steps:
[0073] S1. Weigh Si / C powder (Si content is 7%wt) and binder hydrogenated styrene-butadiene rubber in a mass ratio of 99.9:0.1;
[0074] S2. Si / C powder (Si content is 7%wt) and hydrogenated styrene-butadiene rubber are added to xylene solvent to prepare a carbon layer slurry, and the carbon layer slurry is mixed evenly using a slurry mixer, and then the carbon layer slurry is coated on a copper-lithium composite tape (lithium layer thickness is 50μm±2μm) using a coating machine, and placed in a 60°C vacuum oven for drying for 4 hours to obtain a composite negative electrode sheet, and the thickness of the carbon layer on the composite negative electrode sheet is measured using a digital micrometer to be 25μm±1μm;
[0075] S3. Use an isostatic press to apply a pressure of 10 MPa to the composite negative electrode sheet and maintain the pressure for 30 minutes to obtain a lithium-carbon composite negative electrode sheet with a lithium-philic interface layer LiC6.
[0076] Comparative Example 1
[0077] This comparative example provides a method for preparing a lithium-carbon composite negative electrode sheet, comprising the following steps:
[0078] S1. Weigh artificial graphite and binder hydrogenated styrene-butadiene rubber in a mass ratio of 99:1;
[0079] S2. Add artificial graphite and hydrogenated styrene-butadiene rubber into xylene solvent to prepare carbon layer slurry, use a slurry mixer to mix the carbon layer slurry evenly, and then use a coating machine to coat the carbon layer slurry on a 100 μm thick lithium belt, place it in a vacuum oven at 60° C. and dry it for 2 hours to obtain a composite negative electrode sheet, and use a digital micrometer to measure the thickness of the carbon layer on the composite negative electrode sheet to be 15 μm;
[0080] S3. Use a 5-ton double-roller machine to roll the composite negative electrode sheet to obtain a lithium-carbon composite negative electrode sheet.
[0081] Comparative Example 2
[0082] This comparative example provides a method for preparing a lithium-carbon composite negative electrode sheet, comprising the following steps:
[0083] S1. Weigh natural graphite and binder hydrogenated styrene-butadiene rubber in a mass ratio of 99:1;
[0084] S2. Natural graphite and hydrogenated styrene-butadiene rubber are added to a xylene solvent to prepare a carbon layer slurry, and the carbon layer slurry is mixed evenly using a slurry mixer, and then the evenly mixed carbon layer slurry is dropped on a 100 μm thick lithium belt, and the carbon layer slurry is evenly attached to the lithium belt by a tape casting method, and the carbon layer slurry is placed in a vacuum oven at 60° C. and dried for 2 hours to obtain a composite negative electrode sheet, and the thickness of the carbon layer on the composite negative electrode sheet is measured by a digital micrometer to be 20 μm;
[0085] S3. The composite negative electrode sheet is hot pressed by hot pressing. The upper and lower hot pressing plates are each hot pressed at 30°C and the hot pressing pressure is 20 MPa. The carbon layer is pressed into the metallic lithium to obtain a lithium-carbon composite negative electrode sheet.
[0086] Table 1 shows the parameter characteristics in the preparation of lithium-carbon composite negative electrode sheets of Examples 1-10 and Comparative Examples 1-2.
[0087] Table 1
[0088]
[0089]
[0090] Table 2 shows the thickness characteristics of each layer of the lithium-carbon composite negative electrode sheets of Examples 1-10 and Comparative Examples 1-2 before and after pressurization.
[0091] Table 2
[0092]
[0093]
[0094] Performance testing and analysis
[0095] 1. Test object: lithium-carbon composite negative electrode sheets prepared in Examples 1-10 and Comparative Examples 1-2.
[0096] 2. Test items
[0097] (1) X-ray diffraction (XRD) test
[0098] XRD tests were performed on the lithium-carbon composite negative electrode sheets prepared in Examples 1-10 and Comparative Examples 1-2, respectively. Specifically, Cu Kα wave (wavelength λ=0.154056 nm) was used to diffract the samples, with a scanning angle range of 10°-90° and a scanning speed of 8° / min.
[0099] (2) Scanning electron microscope (SEM) test
[0100] The lithium-carbon composite negative electrode sheets prepared in Examples 1-10 and Comparative Examples 1-2 were tested by scanning electron microscope, respectively, with the acceleration voltage being between 0.3 kV and 30 kV, and the vacuum degree being not less than 0.1 MPa.
[0101] (3) Electrochemical impedance spectroscopy (EIS) test
[0102] The EIS test of the lithium-carbon composite negative electrode sheets prepared in Examples 1-10 and Comparative Examples 1-2 was performed using Shanghai Chenhua CHI660 electrochemical workstation, with a frequency range of 1 MHz-0.1 Hz and a disturbance voltage amplitude of 5 mV.
[0103] (4) Cyclic performance test
[0104] a. Assemble symmetrical cells: Weigh 180 mg of sulfide electrolyte, load it into the mold battery, use a hydraulic press to press at 15 MPa for 5 minutes, obtain an electrolyte sheet and take it out. Then paste a 12 mm thick lithium-carbon composite negative electrode sheet prepared in Example 1-10 or Comparative Example 1-2 on both sides of the electrolyte sheet (Note: at least 11 electrolyte sheets are prepared here, and the lithium-carbon composite negative electrode sheets prepared in the same embodiment or comparative example are pasted on the upper and lower sides of an electrolyte sheet, so that the lithium-carbon composite negative electrode sheets prepared in Example 1-10 and Comparative Example 1-2 are assembled into symmetrical cells). Then use an isostatic press to press at 30 MPa for 10 minutes, assemble into a 2016 model battery, and let it stand for 12 hours to obtain a symmetrical battery.
[0105] b. The symmetrical battery is charged and discharged at a constant current of 1.13 mA for 1 h, and then at a current density of 3 mA cm -2 、Stripping depth 3mAh·cm -2The cyclic charge and discharge test is carried out under the following conditions. The polarization hysteresis voltage is used as the indicator for judging the failure of the symmetrical battery. When the polarization hysteresis voltage is greater than 20mV or the polarization hysteresis voltage is less than 8mV, the battery is considered to be failed. The number of cycles at this time is the cycle life of the symmetrical battery.
[0106] (5) First Coulomb efficiency test
[0107] a. Assemble all-solid-state battery: weigh 180 mg of sulfide electrolyte, load it into the mold battery, use a hydraulic press to press 5 min at 15 MPa, obtain a solid electrolyte sheet and take it out. Then paste a 12 mm thick lithium carbon composite negative electrode sheet prepared in Example 1-10 or Comparative Example 1-2 on both sides of the upper and lower sides of the electrolyte sheet (Note: at least 11 solid electrolyte sheets are prepared here, and the lithium carbon composite negative electrode sheet prepared in the embodiment or comparative example is pasted on one side of the upper and lower sides of a solid electrolyte sheet, so that the lithium carbon composite negative electrode sheets prepared in Example 1-10 and Comparative Example 1-2 are assembled into all-solid-state batteries) and nickel cobalt manganese oxide positive electrode material. Then use an isostatic press to press 10 min at a pressure of 30 MPa, and assemble into a 2016 model battery, let it stand for 12 hours, and obtain a full battery.
[0108] b. At 0.02C (1C = 180mAh g -1 ) at a constant current of 4.2 V, and then discharged to 3 V at a constant current of 0.02 C. The first coulombic efficiency was calculated by the ratio of the first discharge capacity to the first charging capacity in the discharge curve.
[0109] 3. Test results: See Table 3.
[0110] Table 3
[0111]
[0112]
[0113] Combined with Table 3 Figure 1 It can be seen that the lithium-carbon composite negative electrode sheets prepared in Examples 1-7 all include a lithium layer, a carbon layer and a LiC6 layer between the two, and refer to Figure 3The lithium-carbon composite negative electrode sheets prepared in Examples 1-7 were tested by X-ray diffraction (XRD), and all contained lithium peaks, carbon peaks, and LiC6 peaks. Among them, the 001 characteristic diffraction peak formed in the range of 23.66°-24.15° is the LiC6 peak, the 110 characteristic diffraction peak formed in the range of 35.90°-36.39° and the 211 characteristic diffraction peak formed in the range of 64.56°-65.28° are all lithium peaks, and the peak intensity ratio of the 001 characteristic diffraction peak to the 110 characteristic diffraction peak is 0.90-2.57, and the peak intensity ratio of the 001 characteristic diffraction peak to the 211 characteristic diffraction peak is 2.34-4.50, which indicates that the lithium-carbon composite negative electrode sheet contains more LiC6. The LiC6 layer has lithium affinity, can induce uniform deposition of lithium ions, improve the electronegativity of carbon atoms, enhance the bonding between carbon and lithium ions, and effectively inhibit the volume change, dendrite growth and pulverization caused by lithium deposition. At the same time, the appearance of the LiC6 layer causes the carbon peaks in the lithium-carbon composite negative electrode sheet to shift to the left near 43°, 50°, and 74°, and the interlayer spacing d becomes larger (the interlayer spacing of the carbon layer material is 0.354nm, and the interlayer spacing after lithium insertion is 0.370nm), which is more conducive to the insertion and extraction of lithium ions during the charge and discharge process. Therefore, the charge transfer resistance of the lithium-carbon composite negative electrode sheet prepared in Examples 1-7 is low (2-15Ω), and it can be seen in the symmetrical battery test results that the lithium-carbon composite negative electrode sheet prepared using Examples 1-7 improves the cycle life of the battery (more than 2200 cycles). On the basis of the above, the intensity range of the 001 characteristic diffraction peak is 403s -1 -858s -1 , the intensity range of the 110 characteristic diffraction peak is 323s -1 -455s -1 , the intensity range of the 211 characteristic diffraction peak is 172s -1 -260s -1 The thickness of the lithium layer ranges from 6 μm to 100 μm, the thickness of the carbon layer ranges from 1 μm to 50 μm, and the thickness of the LiC6 layer ranges from 1 μm to 50 μm.
[0114] Based on the test results of EIS, cycle performance and first coulombic efficiency, the performance of the lithium-carbon composite negative electrode sheets prepared in Examples 1-2, 4-5 and Example 7 is better than that in Example 2 and Example 4. Therefore, preferably, the peak intensity ratio of the 001 characteristic diffraction peak to the 110 characteristic diffraction peak is 1.80-2.57, and the peak intensity ratio of the 001 characteristic diffraction peak to the 211 characteristic diffraction peak is 3.85-4.50. On this basis, preferably, the intensity range of the 001 characteristic diffraction peak is 820s -1 -858s -1 , and the intensity range of the 110 characteristic diffraction peak is 323s -1 -455s -1, and the intensity range of the 211 characteristic diffraction peak is 187s -1 -213s -1 The thickness of the lithium layer ranges from 6 μm to 100 μm, the thickness of the carbon layer ranges from 2.5 μm to 50 μm, and the thickness of the LiC6 layer ranges from 3 μm to 50 μm.
[0115] For Example 8, although it contains Li C6 peak, the peak intensity ratio of its 001 characteristic diffraction peak to the 110 characteristic diffraction peak is 0.7 (lower than 0.90-2.57 of Example 1-7), and the peak intensity ratio of its 001 characteristic diffraction peak to the 211 characteristic diffraction peak is 1.9 (lower than 2.34-4.50 of Example 1-7). Combined with Table 2, it can be seen that the thickness of the LiC6 layer of the lithium-carbon composite negative electrode sheet of Example 8 is only 0.4μm (lower than 1μm-50μm of Example 1-7). It shows that although the Li C6 layer is formed in Example 8, the content of the Li C6 layer is relatively small, and the induction of the uniform deposition of lithium ions is relatively poor, and the volume change, dendrite growth and pulverization caused by lithium deposition cannot be effectively suppressed. In addition, the thinner Li C6 layer has less effect on the interlayer spacing, which is not conducive to the insertion and extraction of lithium ions during charging and discharging. Therefore, the charge transfer resistance of the lithium-carbon composite negative electrode sheet prepared in Example 8 is higher than that of Examples 1-7, and in the symmetrical battery test results, the cycle life of the lithium-carbon composite negative electrode sheet prepared using Example 8 is lower than that of Examples 1-7.
[0116] For Example 9, although it was rolled and isostatically pressed to form a Li C6 layer and obtain a lithium-carbon composite negative electrode sheet with lower impedance, the peak intensity ratio of its 001 characteristic diffraction peak to the 110 characteristic diffraction peak was 2.64 (higher than 0.90-2.57 of Example 1-7), and the peak intensity ratio of 001 characteristic diffraction peak to 211 characteristic diffraction peak was 4.61 (higher than 2.34-4.50 of Example 1-7). This is because the isostatic pressure of Comparative Example 3 is too large, causing the lithium-carbon composite negative electrode sheet to crack and cannot be used. Therefore, on the basis of rolling / hot pressing and isostatic pressing, it is also necessary to ensure that the isostatic pressure is moderate to avoid damaging the electrode sheet.
[0117] For Example 10, the peak intensity ratio of its 001 characteristic diffraction peak to its 110 characteristic diffraction peak is 2.63 (higher than 0.90-2.57 of Example 1-7), and the peak intensity ratio of its 001 characteristic diffraction peak to its 211 characteristic diffraction peak is 6.58 (higher than 2.34-4.50 of Example 1-7). This indicates that although Example 10 is subjected to isostatic pressing, since no rolling or hot pressing is performed, there is a large gap between the lithium layer and the carbon layer, and the contact between the two is poor. When the isostatic pressing is performed later, the lithium layer cannot be effectively embedded in the carbon layer and chemically react, so that the lithium-carbon composite negative electrode sheet has a higher impedance, and therefore the cycle performance and the first coulombic efficiency of the lithium-carbon composite negative electrode sheet used in the all-solid-state battery are poor.
[0118] Further analysis, referring to Table 1 and Table 3, by comparing Examples 1-7 and Comparative Examples 1-2, it can be seen that Examples 1-7 were subjected to isostatic pressing after rolling or hot pressing, while Comparative Examples 1-2 were only subjected to rolling or hot pressing without isostatic pressing. Therefore, the isostatic pressing of Examples 1-7 can embed lithium metal into the carbon layer under isotropic, ultra-high molding pressure, and chemically react to form a lithium-philic LiC6 layer, while Comparative Examples 1-2 were not subjected to isostatic pressing, and rolling or hot pressing can only physically combine the lithium layer and the carbon layer, and cannot form a lithium-philic LiC6 layer. Therefore, the lithium-carbon composite negative electrode sheet prepared in Comparative Examples 1-2 cannot effectively induce uniform deposition of lithium ions, and is not conducive to the embedding and extraction of lithium ions during charging and discharging, so that the lithium-carbon composite negative electrode sheet prepared in Comparative Examples 1-2 reduces the cycle performance of the battery.
[0119] Moreover, since the LiC6 layer is not formed in Comparative Example 1-2, when the lithium-carbon composite negative electrode sheet of Comparative Example 1-2 is pressed during the process of assembling into an all-solid-state battery, its lithium layer is easily deformed, and is easily embedded in the pores of the carbon layer, and even extends into the solid electrolyte layer, and the positive electrode will also squeeze toward the solid electrolyte layer during the pressing process, which may cause a short circuit between the negative electrode lithium layer and the positive electrode, resulting in short circuit self-discharge in the all-solid-state battery, making the coulomb efficiency of Comparative Example 1-2 lower than that of Example 1-7. Therefore, the lithium-carbon composite negative electrode sheet of the present invention is used in an all-solid-state battery to improve the first coulomb efficiency of the battery, reduce the risk of short circuit in the battery, and improve the practicality and mass production of the lithium negative electrode in the all-solid-state battery system.
[0120] The technical means disclosed in the scheme of the present invention are not limited to the technical means disclosed in the above-mentioned implementation mode, but also include technical schemes composed of any combination of the above-mentioned technical features. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also regarded as the protection scope of the present invention.
Claims
1. A lithium-carbon composite negative electrode sheet, characterized in that: include: A lithium layer, a carbon layer and a LiC6 layer, wherein the LiC6 layer is disposed between the lithium layer and the carbon layer, and the X-ray diffraction spectrum of the lithium-carbon composite negative electrode sheet has a 001 characteristic diffraction peak in the range of 23.66°-24.15°; The X-ray diffraction spectrum of the lithium-carbon composite negative electrode sheet has a 110 characteristic diffraction peak in the range of 35.90°-36.39°, and the peak intensity ratio of the 001 characteristic diffraction peak to the 110 characteristic diffraction peak is 0.90-2.57; The X-ray diffraction spectrum of the lithium-carbon composite negative electrode sheet has a 211 characteristic diffraction peak in the range of 64.56°-65.28°, and the peak intensity ratio of the 001 characteristic diffraction peak to the 211 characteristic diffraction peak is 2.34-4.
50.
2. A lithium-carbon composite negative electrode sheet according to claim 1, characterized in that: The thickness of the lithium layer is 6-100 μm, the thickness of the carbon layer is 1-50 μm, and the thickness of the LiC6 layer is 1-50 μm.
3. A lithium-carbon composite negative electrode sheet according to claim 2, characterized in that: The thickness of the lithium layer is 10-90 μm, the thickness of the carbon layer is 3-20 μm, and the thickness of the LiC6 layer is 3-20 μm.
4. The lithium-carbon composite negative electrode sheet according to claim 1, characterized in that: The peak intensity of the 001 characteristic diffraction peak is 403-858s -1 The peak intensity of the 110 characteristic diffraction peak is 323-455s -1 .
5. The lithium-carbon composite negative electrode sheet according to claim 1, characterized in that: The peak intensity of the 211 characteristic diffraction peak is 172-260s -1 .
6. The lithium-carbon composite negative electrode sheet according to claim 1, characterized in that: The lithium layer includes a lithium metal layer or a lithium alloy layer.
7. The lithium-carbon composite negative electrode sheet according to claim 1, characterized in that: The carbon layer comprises at least one of artificial graphite, natural graphite and Si / C, wherein the content of Si in the Si / C is 5-20%wt.
8. A battery, characterized in that: A lithium-carbon composite negative electrode sheet comprising any one of claims 1 to 7.
9. An all-solid-state battery, characterized in that: A lithium-carbon composite negative electrode sheet comprising any one of claims 1 to 7.
Citation Information
Patent Citations
Composite metal lithium cathode with lithium-carbon composite interface layer and preparation method thereof
CN109686921A
Lithium negative pole piece, preparation method thereof and lithium battery
CN111430663A